Handy Lanyard / Norfadzilah Amirah Mohammad Fadzli … [et al.] - Mohammad Fadzli, Norfadzilah Amirah; Ab Malek, Nur Adibah; Yaacob, Nazirah; Mohd Nor Shuhaimi, Nadia Nisa; Wan Hasan, Wan Hasmat (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2022)
After nearly two years of combating the pandemic, the transition to the endemic phase is an exit strategy that will let Malaysians resume their normal lives. This phase helped business owners satisfy the needs and wants of customers. We at Urban Space Ent could not let this chance pass us by, therefore we took care of the problems that students and employees had on a daily basis with our product innovation, the Handy Lanyard. Allowing you to get rid of the clutter in your life is our most important objective. The Handy Lanyard has two anatomical components: the lanyard strap, which represents the cable, and the lanyard body, which functions as a mini power bank and refilling spray container for hand sanitizer. When it comes to the lanyard's body, we solely utilized lightweight and durable materials. The lanyard cable, on the other hand, is constructed from materials such as ABS and polyester, which do not tangle as easily as other materials. The functionality provided by the Handy Lanyard makes life easier and more convenient. Due to its versatility, customers can use it as both a lanyard and a power bank with a refillable hand sanitizer spray container that can be brought anytime and everywhere. Purchasing this item is a no-brainer, especially in light of the current endemic situation. Our goal is to create a one-of-a-kind product for Malaysia and, preferably, the world. It is also the objective of our company: to supply consumers with new solutions based on timeless, high quality products that can be used by everyone.